Math remediation for the college bound : how teachers can close the gap, from the basics through algebra - Khatri, Daryao S., 1945- (Rowman & Littlefield Education, 2012)
"Algebra is the language that must be mastered for any course that uses math because it is the gateway for entry into any science, technology, engineering, and mathematics (STEM) discipline. This book fosters mastery of critical math and algebraic concepts and skills essential to all of the STEM disciplines and some of the social sciences"--Provided by publisher